EFEKTIVITAS PARTISIPASI MASYARAKAT DALAM PENINGKATAN PELAYANAN PUBLIK DI KELURAHAN TOBEKGODANG KECAMATAN TAMPAN - marlinda, pebriana; eka, eka; ferizko, adia (Jurnal Niara, 2017)
This study aims to see who is involved in public services in the Tobekgodang District of Tampan District, which has been regulated in the Regulation of the Minister of State for Administrative Reform No. 13 of 2009 concerning Guidelines for Improving the Quality of Public Services. The design of this study uses descriptive qualitative methods that will reinforce and review the data in general in the form of documents relating to public facilities within the scope of public services Tobekgodang District Tampan District. In addition, so that the research objectives can be used also use primary data in the form of interviews with research informants, namely: Head of Tobekgodang Village, Secretary of Tobekgodang Village, Tobek godang Village Staff and Tobekgodang Village Community. The results of this study indicate that the participation of the community in Tobekgodang Subdistrict, Tampan District has been effective in improving public services in Tobekgodang Subdistrict, Tampan District.